Sorption cable sensor with large sensing range and fields of its application - S. A. Kudzh; V. S. Kondratenko; A. Yu. Rogov; Yu. I. Sakunenko; E. A. Druzhinin (Российский технологический журнал)
The paper discusses the existing approaches to the use of point and cable sensors to control leaks and humidity. The principal disadvantages of monitoring systems based on them are shown: when detecting leaks, there is a delay in the response time due to the condition of fluid accumulation around the sensors; when controlling the humidity of extended environments, it becomes necessary to install a large number of point sensors with individual switching channels; there is no universal sensor for monitoring leaks and humidity. An alternative solution is proposed - a sorption cable sensor with a large sensitivity range, which, as a leak detector, can be placed anywhere in 3D space where leakage is most likely, and as a linear humidity sensor, it can replace point sensors in an extended control zone. The research results of the developed cable sensors confirm their high sensitivity, speed and relaxation ability to recover (dry) after leaking. The areas of application considered in the article, examples of the implementation of a sorption cable sensor in a system for monitoring leaks and air humidity of computing nodes with liquid cooling of Russian supercomputers testify to the high efficiency and development potential. Based on sorption cable sensors, it is possible to build effective systems for early detection of leaks by the first signs of their manifestation, environmental humidity control systems and universal leakage control systems, steam breakthroughs and the level of relative humidity. Reducing the time for detecting leaks and steam breakthroughs will allow taking preventive measures to prevent the development of damage, and the use of cable humidity sensors instead of distributed point sensors will dramatically reduce the cost of organizing humidity monitoring of extended environments.